Model prototype of a solar tracking system supplying electrical power for sensors used in a natural disaster monitoring system - Aliyah Zainal Abidin, N.; Ghani, Z.A. (Penerbit Universiti Kebangsaan Malaysia, 2023)
Sun is the universe main source of energy. This energy can be converted to useful electrical energy by the utilization of solar panels or photovoltaic (PV) during the daytime with the presence of suitable sun irradiation level. It is important that during the energy conversion process, suitable methods are employed to extract as much energy as possible from the PV panels. Some issues affecting PV performance are the accuracy of the panel’s orientation and tilt angle with respect to the sun position. This causes PV to operate with lower efficiency, thus generating low output power compared to its rated capacity. One of the approaches to this issue is to constantly maintain a perpendicular profile of PV panels towards the sun direction as to capture the sun energy as much as possible, thus increases the PV efficiency. To do so, the conversion system needs a tracking mechanism to help the solar panel to constantly follow the sun’s direction, enhancing the achievement of higher PV efficiency. For this reason, a model prototype has been designed and developed which consists of a dual-axis solar tracking system, with two axis movement direction from east to west and north to south by utilizing the Light Dependent Resistors (LDRs) sensors. This tracking system is developed using Arduino UNO as the microcontroller that allows the PV panel to move optimally towards the high intensity of sunlight via four LDRs and two servo motors. To analyze the PV tracker’s performance, a monitoring system is implemented using ThingSpeak platform as the Internet of Things (IoT) platform interfacing with the controller Node MCU ESP8266. This monitoring system records the data of the PV energy parameters from the sensors’ output employed in this prototype. To assess the system efficacy, the dual-axis tracking system is compared with the single-axis tracking system. The result showed that the dual-axis tracker has efficiencies of 68.46% which is higher compared to that’s of the single-axis tracker. Implementation of the real-time monitoring system has shown a practical and handy way to analyze and monitor the solar tracking system’s performance.